“Fatal attraction” and level-k thinking in games with non-neutral frames - Crawford, V (Elsevier, 2018)
Traditional game theory assumes that if framing does not affect a game’s payoffs, it will not influence behavior. However, Rubinstein and Tversky (1993), Rubinstein, Tversky, and Heller (1996), and Rubinstein (1999) reported experiments eliciting initial responses to hide-and-seek and other types of game, in which subjects’ behavior responded systematically to non-neutral framing via decision labelings. Crawford and Iriberri (2007ab) proposed a level-k explanation of Rubinstein et al.’s results for hide-and-seek games. Heap, Rojo-Arjona, and Sugden’s (2014) criticized Crawford and Iriberri’s model on grounds of portability. This paper clarifies Heap et al.’s interpretation of their results and responds to their criticisms, suggesting a way forward.